Job mobility and segmentation in Australian city labour markets. (7th July 2008) - Bill, Anthea; Mitchell, Bill; Welters, Riccardo
Cities are said to have afforded workers higher earnings and greater opportunity to appropriate productivity gains through job mobility. The flipside of flexibility is perhaps more insecurity, associated with casualisation and intense competition for low-skilled positions. This article examines whether cities do promote greater levels of mobility and whether workers in the primary and secondary segments display different patterns of job transition in urban vs. non-urban areas. We find evidence of higher job mobility in urban areas associated with both increased confidence that search will locate a new job and heightened fear of losing one's current job. Controlling for other factors, confidence (linked to upward job mobility), is higher in the primary segment of urban labour markets, but so is fear of losing one's job (linked to downward job mobility). Thus, the primary labour market of urban areas may be particularly susceptible to the adverse dynamics associated with increased mobility.